Examining of Relationships Among Traits Using Correlation, Path and Principal Components Analysis Methods in Turkish Opium Poppy (Papaver somniferum L.) Cultivars - Nimet Kara; Hasan Baydar (Journal of Agricultural Sciences)
Opium poppy is an important medicinal plant because of its very valuable pharmaceutical alkaloids such as morphine, codeine, and papaverine, etc. The research was carried out with the aim to examining the relationships between capsule yield, some other yield and quality traits by means of correlation, path and principal components analysis (PCA) in fifteen opium poppy (Papaver somniferum L.) cultivars registered in Turkey. The experiments were conducted designed according to a randomized complete block with three replications during 2012/13 and 2013/14 growing years in Isparta conditions. In the research, there were significant positive correlations between capsule yield and capsule width, and 1000 seed weight, while insignificant associations between capsule yield (non-seed) and seed yield, plant height, capsule number, capsule length, oil yield, and morphine content were determined. The significant and high negative correlation was determined between capsule yield with oil content. According to the path analysis, the highest positive direct effect on capsule yield was seed yield (48.202%), and the highest positive indirect effect on capsule yield was capsule width (47.877%) via seed yield. The ten PCA components (PC1 to PC10) created 90.09% of the total variation among traits in poppy cultivars. PC1, PC2, PC3, and PC4 with values of 52.0%, 16.9%, 11.8%, and 10.2%, respectively contributed to the total PCA value, and plant height, capsule width, capsule number, and 1000 seed weight were found to be effective components on the yield in PCA analysis. The bi-plot analysis showed that capsule number, capsule length, seed yield, and oil yield created the same group and plant height and capsule width were another group, and these characters showed stability for the cultivars. The according to the results of the correlation, path, and PCA, capsule width and 1000 seed weight were effective components on capsule and seed yields of the opium poppy.  ysis